2018
DOI: 10.1039/c7ra13436c
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, polaron formation, and functional properties in transition-metal tungstates

Abstract: This work establishes a relationship between the electronic structure, polaron formation, and electrochemical activity in transition-metal tungstates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…In addition, the electronic structure of NiWO 4 was obtained. For NiWO 4 , the CB predominantly consists of W 5d orbitals and Ni 3d orbitals, while the VB primarily consists of Ni 3d orbitals and O 2p orbitals [ 105 ]. It was found that the VB composition of NiWO 4 is different from those of FeWO 4 and CoWO 4 , which is related to the energy level distribution of the orbital electrons around the metal ions.…”
Section: Ternary Mwo 4 Photocatalysts (M = Bivalenmentioning
confidence: 99%
“…In addition, the electronic structure of NiWO 4 was obtained. For NiWO 4 , the CB predominantly consists of W 5d orbitals and Ni 3d orbitals, while the VB primarily consists of Ni 3d orbitals and O 2p orbitals [ 105 ]. It was found that the VB composition of NiWO 4 is different from those of FeWO 4 and CoWO 4 , which is related to the energy level distribution of the orbital electrons around the metal ions.…”
Section: Ternary Mwo 4 Photocatalysts (M = Bivalenmentioning
confidence: 99%
“…28 Hoang et al, in 2018, carried out a hybrid density-functional analysis of the electronic structure and established that a polaron was formed through the underlying mechanism for the existence of p-type semiconductivity in CoWO 4 . 29 The conductance of CuWO 4 is attributed to the hopping of small polarons. In 2017, Hoang et al conducted a first-principles study of iron tungstate (FeWO 4 ) and manganese tungstate (MnWO 4 ) to attain a detailed understanding of their properties such as lattice parameters, static dielectric constants, and band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…The role of polarons as charge-carrying defects in (thermally activated) electronic conduction in complex materials will be discussed in section 6. The interplay between electronic structure and polaron formation (and hence presence of active redox centers) has also been shown to be essential to the understanding of materials for pseudocapacitors [81,82] and solid-oxide fuel cells [64].…”
Section: Electronic Structure Vis-à-vis Polaron Formationmentioning
confidence: 99%